SURAT PERINTAH PENGHENTIAN PENYIDIKAN (SP3) DALAM PERKARA TINDAK PIDANA KORUPSI - Jamsianah, Etik; Artha, I Gede; Adiyaryani, Ni Nengah (Kertha Wicara : Journal Ilmu Hukum; Vol 1 No 01 (2012))
KUHAP is not formulating clearly what it means with the termination ofinvestigation but instead only providing the formulation regarding theinvestigation only. Besides the regulation regarding the procedure oftermination of prosecution has been arranged more detail and clearer, whileregarding the termination of investigation the regulation is not complete.However, it can be formulated that the termination of investigation is theaction of investigator to cease the investigation of an event allegedly to be acriminal act, due to “make it clear that an event is allegedly and to determinea subject as the suspect that there is not enough evidence or from aninvestigation it is found that the event is not a criminal act or the investigationis terminated for the sake of law”. It is stated in KUHAP article 109subsection (2). In contrast to Public Prosecutor and Police Department as aninvestigator of a criminal act, Corruption Eradication Commission (KPK)agency which is the institution or state’s agency formed by the Law No.30year 2002 regarding Criminal Act of Corruption Eradication Commission isnot authorized to issue a Warrant of Investigation Termination (SP3) in eachof the investigation conducted. It has been confirmed in Article 40 the LawNo.30 year 2002 regarding Criminal Act of Corruption EradicationCommission.
Keywords: Investigation, The Termination of Warranty of Investigation, Distinctive Criminal Act, Corruption